The Multiple Faces of Programmed Cell Death Ligand 1 Expression in Malignant and Nonmalignant Cells. Issue 4 (April 2019) - Parra, Edwin R.; Villalobos, Pamela; Rodriguez-Canales, Jaime
Abstract : Preliminary data suggest that tumor expression of programmed cell death ligand 1 (PD-L1) protein in human cancers, as determined by immunohistochemistry in formalin-fixed, paraffin-embedded tissue samples, may predict clinical response to anti-PD-1/PD-L1 therapy. PD-L1 is not a specific tumor marker and its expression is also observed in various nonmalignant cells, such as macrophages and lymphocytes, causing confusion in immunohistochemistry analysis when these inflammatory cells are overlapping with tumors cells. The aim of the current study was to examine PD-L1 expression in formalin-fixed, paraffin-embedded malignant and nonmalignant cells from human tumors to establish potential characteristic patterns of PD-L1 expression in tumor tissues. We used a commercial PD-L1 clone (E1L3N) previously validated in our laboratory to characterize PD-L1 expression in surgically resected lung adenocarcinomas, lung squamous cell carcinomas, malignant melanomas, renal cell carcinomas, hepatocellular carcinomas, and ductal breast carcinomas. We observed different patterns of PD-L1 expression by malignant cells and nonmalignant cells as membrane, cytoplasmic, and nuclear expression. The distribution of expression was variable including the entire malignant cells population, heterogonous with random distribution, peripheral distribution, minimal expression by few cells and negative expression. Similar, nonmalignant cells showed randomly and peripherally distribution through the tumors. We concluded that the PD-L1 cell protein expression patterns and distributions are variable and differ between resected tumor specimens. The expression and distribution pattern described here provide a useful knowledgment of PD-L1 expression in tumor samples.